Teratoid Cyst of the Postauricular Region: The First Ever Case Report - Sabin Ranabhat; Mamata Tiwari; Sushna Maharjan (Hindawi Limited, 2017)
Rudolf Virchow is considered to be the first scientist to have used the word sebaceous cyst. It was thought that these lesions occurred due to retention of sebaceous secretion consequent to obstruction of sebaceous ducts of sebaceous glands, although that was found not to be the case. In all these cysts, the cavity is filled with keratin. There are six types of keratin-filled cysts, namely, epidermoid, dermoid, teratoid, keratinous, trichilemmal, and teratoma cyst, which have one common name "dermoid cyst." Of the six, teratoid cyst is the least common. In contrast to other dermoid cysts, teratoid cysts contain tissue elements derived from all the three germ layers, namely, ectoderm, mesoderm, and endoderm. Teratomas can be differentiated from teratoid cysts by the fact that recognizable organ structures may be found in the former; examples include teeth and skin. Teratoid cysts can develop anywhere in the body but rarely arise in the head and neck region. They have never been reported in the postauricular region. In this case report, we present a case of teratoid cyst in the postauricular region in a 21-year-old female. The significance of this case lies in its rarity.